Free Day Secondary Education Funding and Student Retention across Gender in Migori County, Kenya - Achieng, Madeleine Sophie Barat; Harriet Njui (IJRDO- Journal of Educational Research, 2020)
Considerable progress has been made worldwide in enrolment of boys and girls both at primary and secondary levels. However studies indicate that the actual completion rates at secondary school remain low especially for girls. While the Kenyan government has put in place impressive education policy that details how gender inequality should be addressed, the implementation of the same has remained elusive. This study was anchored on systems and retention theories and sought to add knowledge and literature related to free day secondary education and student retention. The study targeted 215 public day secondary schools. The actual sample was of 19 schools, 228 students, 76 class teachers, 19 principals, 31 parents and 1 Quality Assurance and Standards Officer. The study adopted a convergent parallel mixed method design using cross sectional survey for the quantitative method and a case study design for the qualitative method. Data were collected using questionnaires, interview guides, document analysis guide and focus group discussions. Descriptive statistics were generated through using MS Excel 2018 and SPSS version 21. Qualitative data from interviews and focus group discussions were analysed thematically. The report was given in narrative form and direct quotes. The findings relieved that boys are 2.84 times more likely to be followed-up in cases of absence compared to girls. Girls seem to face challenges such as early marriages and lack of sanitary towels among others, which keep them away from school. The study recommended that the government should set aside funds to support vulnerable boys and girls in public secondary schools as an intervention for promoting equity in secondary education